1978
DOI: 10.1515/zna-1978-0308
|View full text |Cite
|
Sign up to set email alerts
|

Steric Interaction of Fluid Membranes in Multilayer Systems

Abstract: The out-of-plane fluctuations of fluid membranes are sterically hindered in multilayer systems. The repulsive interaction associated with the steric or excluded-volume effect is studied theoretically by two methods. The interaction energy per unit area of membrane is derived as a function of temperature, membrane curvature elasticity and mean membrane spacing; it is inversely proportional to the square of the latter. Steric repulsion is estimated for lecithin bilayers in water. There and in other cases, it may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
435
2
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,061 publications
(471 citation statements)
references
References 14 publications
14
435
2
8
Order By: Relevance
“…In the fully hydrated pure phospholipid bilayers, the strength of undulatory fluctuations is proportional to the square of the temperature (Helfrich, 1978). These fluctuations cause disorder in the relative position of unit cells (long-range disorder) resulting in broadening of diffraction peaks, and the magnitude of this effect increases with increasing diffraction order (Zhang et al, 1996;Petrache et al, 1998;Gordeliy et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In the fully hydrated pure phospholipid bilayers, the strength of undulatory fluctuations is proportional to the square of the temperature (Helfrich, 1978). These fluctuations cause disorder in the relative position of unit cells (long-range disorder) resulting in broadening of diffraction peaks, and the magnitude of this effect increases with increasing diffraction order (Zhang et al, 1996;Petrache et al, 1998;Gordeliy et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…NMR investigations revealed that water molecules at the lipid water interface are partially oriented due to an interaction with the lipid water interface (Gawrisch et al 1992) which could be the origin of a repulsive hydration force (Leikin and Kornyshev 1990). But the chemical potential of water may also be lowered by bilayer undulations (Helfrich 1978), by electrostatic repulsion between charged bilayers (Cowley et al 1978) and by entropically-driven movements of individual lipids or lipid segments along the bilayer normal (Israelachvili and Wennerström 1996). Repulsive forces between bilayers play a major role in cell fusion, one of the most fundamental biological processes (Arnold and Gawrisch 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Ramaswamy argued that the suppression of undulations triggers the transition [13]. Lyotropic lamellar phase is stabilized by a steric repulsive force arising from undulation fluctuation [18]. As a result of the suppression of the undulation fluctuation by shear flow, reduction of the repulsive force will induce the instability.…”
Section: Resultsmentioning
confidence: 99%
“…The HelfrichHurault effect is undulation instability of the smectic phase subjected to the external electric or magnetic field [17]. In the thermal equilibrium state, the undulation fluctuation yields repulsive Helfrich interaction between membranes which stabilizes the lamellar phase [18]. Suppression of the undulation fluctuation by shearing will reduce the repulsive force and destabilize lamellar membranes which causes the reduction of layer spacing.…”
Section: Introductionmentioning
confidence: 99%